THE ECONOMIC VALUE OF HYDROLOGICAL SERVICES IN MENDALAM SUB WATERSHED, KAPUAS HULU REGENCY, WEST KALIMANTAN, INDONESIA - Roslinda, Emi; Yuliantini, Yuliantini (Secretariat of Forestry Research and Development Agency, 2014)
Forest ecosystem supports almost all ofÂ the needs ofÂ human being through its contribution ofÂ tangible and intangible values.Â Currently, the intangible values have gained less attention than the tangible values that causeÂ underestimation ofÂ the total value ofÂ the forest conversion into other more tangibly profitable usages, and miss-management ofÂ the forest. One ofÂ the important intangible values is the hydrological value that has been hardly calculated until now.Â This research the intangible values ofÂ water for household, transportation, agriculture and fishing in Mendalam Sub Watershed, Kalimantan. The economic values calculated based on market prices, opportunity costs and consumerâs surplus methods. The results showed that based on theÂ Â Â opportunity cost method the economic values ofÂ the hydrological services was about Rp 8,043,706,237.50 per year. Meanwhile, the economic values ofÂ the hydrological services based on the consumerâs surplus method gave lower value than the former method, i.e. Rp 8,031,351,664.60 per year. This study showed that the economic value ofÂ the hydrological services was very high, which has not been included in the calculation yet. However, without trees there would be no forest and all other values included water value would not exist. Consequently, current forest management should put forest ecosystem as important to consider.